Dynamic Dirt: Medieval Holy Dust, Ritual Erosion, and Pilgrimage Ecopoetics - Susan Signe Morrison (Open Library of Humanities, 2019)
Environmental citizenship has intellectual roots extending into the Middle Ages. We need to get down and dirty—literally. This article—rooted in vibrant materialist intersections with medieval pilgrimage poetry—transverses literary and ecological paths as it explores pilgrimage ecopoetics. From the Middle Ages to today, voluntary migrants in the form of pilgrims cause environment degradation, everything from waste disposal to soil erosion on frequented paths. Focusing on dirt in which pilgrimage paths have sprung up and dirt used as healing relic, we come to understand actants like dirt and holy dust in a new way. Tomb dust and holy dirt convey an agency that catalyzes our understanding of pilgrimage as materially grounded in the earth. Things are not mere objects, but possess independence from us. Possessing agency, matter itself is not static but generative. Dirt’s extended fellows include reviled trash, waste, and crap. A modern-day pilgrimage shrine, the Cathedral of Junk in Austin, TX, is a refuse pile of rejected garbage. Sustainably reused by the creator, this shrine perfectly realizes a Judeo-Christian ethos of charity. See in this way, dirt—normally reviled as abject, even ‘out of place’ (Douglas 1966/2002: 44)—can be viewed as positive, even sacred. Like waste poetry, dirt ultimately heals homeopathically for both spirit and body.